The effect of a vegetation period on productivity, protein and oil percentage in grain of the collection soybean samples - A. R. Ashiev; A. V. Chegunova; M. V. Skulova; K. N. Khabibullin; N. S. Kravchenko (Зерновое хозяйство России, 2021)
The purpose of the current study was to identify the effect of the length of a vegetation period of the collection soybean samples on grain productivity and quality. The study was carried out in the southern part of the Rostov region in the fields of the FSBSI Agricultural Research Center “Donskoy” in 2018–2020. The climate is semi-arid with moderately hot summers. The soil is ordinary thick calcareous heavy loamy blackearth (chernozem). The forecrop was winter wheat. The objects of the study were collection soybean samples of the ARIGPR named after N.I. Vavilov. The study was carried out on 75 samples, including 52 middle early samples with 110-120 days of vegetation and 23 middle maturing samples (120-130 days of vegetation), differing in morphobiological and economically valuable traits. The analysis of a vegetation period, grain productivity and quality of the collection soybean samples has shown that in the southern part of the Rostov region the most variable trait was grain productivity (Cv = 22.5%). The less variable characteristics were protein percentage in grain (Cv = 3.8%), a vegetation period (Cv = 4.2%) and oil content in grain (Cv = 5.3%). There has been identified a positive effect of the length of a vegetation period of soybeans on grain productivity and oil content in grain for both groups of maturity, protein percentage in both groups of maturity having a negative dependence on a vegetation period. The study has shown that in the middle early group, the largest grain productivity was obtained with 117 and 118 days of vegetation, the highest protein percentage with 110 and 114 days of vegetation, and the largest oil content in grain with 118 and 120 days of vegetation. In the middle maturing group, the maximum productivity indicators were obtained for the samples with 126 and 130 days of vegetation, the maximum protein percentage with 122 days of vegetation and the maximum oil content in grain with 123 and 130 days of vegetation. The samples showing the maximum indicators will be included in further soybean breeding.